(untitled) (Proceedings of the International Conference on Education, 2021)
The international exchange for undergraduate students is a life-changing experience, an opportunity to interact with others and develop intercultural skills while learning. Nevertheless, the deficit in student participation in internationalization activities demands new formats that offer this academic practice in a virtual environment. Adjacent to this scenario, the greatest impact of the COVID-19 pandemic on higher education was face-to-face exchanges. Therefore, academic programs as Global Classroom was the only way for an international exchange amid the pandemic. The objective of this study was to assess the perceptions of the students about an implementation of a virtual international exchange shared with students from Mexico and Ecuador, focused on this contribution as an educational innovation to promote learning in multicultural and interdisciplinary skills. The study considered a quantitative approach to analyze a student’s perception of the experience, and the design was descriptive and cross-sectional. The sample were 44 students enrolled in the experience in the August-December semester in 2020, 22 from Mexico and 22 from Ecuador. The instrument was made of 5 items in which the participants shared their experience regarding the different tools and activities, and their contribution to the educational objectives. Results show that the students valued the intercultural experience positively and the contribution of the different free-access educational technology tools to develop synchronous and asynchronous activities. Other disciplines and institutions can learn from this implementation to design remote educational environments that offer this internationalization experience for learners even after the pandemic.